From manufacturing-led export growth to a twenty-first-century inclusive growth strategy: Explaining the demise of a successful growth model and what to do about it - Joseph E. Stiglitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Success in development over the past half-century was based on manufacturing-led export growth. Because the share of global employment in manufacturing will decline, manufacturing won't play the same role in the coming decades. An increase in manufacturing employment won't suffice to meet the need for new jobs, especially in Africa with its burgeoning population. There has to be another strategy. I deconstruct what enabled manufacturing to generate growth and structural transformation. It simultaneously provided needed foreign exchange, promoted learning, and provided employment. The new strategy I propose is more multi-pronged, addressing separately, in different sectors, the challenges of learning, foreign exchange, and employment. A carefully designed, co-ordinated multi-sector strategy, with sectoral policies in agriculture, natural resources, manufacturing, and especially services, has the prospect of attaining the same success as the old manufacturing export-led strategy. The development state will continue to be central, but has to be redefined. The new development strategies will require greater balance between the market, the state, and the community, a perspective articulated in the Stockholm Statement.
Keywords: O14; O24; O55; O57; 330; economic development; Stockholm Statement; industrial policy; dynamic comparative advantage; global reserve system